Romanian Universities Face to the Networked Learning Reality - Mohora, Cristina; Ispas, Constantin; Zapciu, Miron (Proceedings of the International Conference on Networked Learning, 2000)
This paper reports some of the findings and problems of a ODL Socrates project which is conducted in the POLITEHNICA University of Bucharest and is entitled: "FAVIRinternational virtual network for the future enterprise. The virtual network FAVIR founded in 1999 between 4 organizations in Europe (3 universities and one organization specialized io multimedia and new technologies) will improve the relations and experience in the networked learning between Greece, France, Italy and Romania. The object of the project is to integrate the partners, the pedagogical experience specific to each of them and to disseminate ideas and experiences in the networked learning (favir@egroups.com). The fields of activity arc very important because they define a virtual network, which correspond to the virtual enterprise principles.